Therapeutic modalities : the art and science - Knight, Kenneth L.; Draper, David O. (Baltimore, MD : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
Authored by two leading researchers in the athletic training field, this Second Edition, provides the knowledge needed to evaluate and select the most appropriate modalities to treat injuries. The authors use an informal, student-friendly writing style to hold students' interest and help them grasp difficult concepts. The unique approach of the text teaches aspiring clinicians both the how and the why of therapeutic modality use, training them to be decision-making professionals rather than simply technicians. The Second Edition is revised and expanded to include the latest research in therapeutic modalities. New material has been added on evidence-based practice, and other areas, such as pain treatment, are significantly expanded. It retains the successful format of providing the necessary background information on the modalities, followed by the authors''5-Step Application Procedure.' New photos, illustrations, and case studies have also been added.
Therapeutic modalities : what they are and why they are used -- Evidence based practice -- General application procedures -- Injury record keeping -- Tissue response to injury: inflammation, swelling, and edema -- Immediate care of acute orthopedic injuries -- The healing process -- Understanding pain and its relationship to injury -- Relieving orthopedic injury pain -- Principles of heat for thermotherapy -- Superficial thermotherapy application -- Cryotherapybeyond immediate care -- Cryotherapy application for post-immediate care -- Therapeutic ultrasound principles and application -- Diathermy principles and application -- Principles of electricity for electrotherapy -- Electrotherapy application -- Therapeutic massage -- Spinal traction -- Laser and light therapy by Knight/Hopkins -- Differential application of therapeutic modalities -- Case studies using therapeutic modalities.
This book includes online access at http://thepoint.lww.com/active, please refer library staff for the password
Includes bibliographical references and index.
Keywords: Physical Therapy Modalities; Orthopedic Procedures -- methods; Physical therapy